Modulação da orientação temporal e espacial da atenção por meio de estimulação transcraniana por corrente contínua - Araujo, Ricardo Rafael de (2011)
Attention can be understood as a set of neural mechanisms that enhance the processing of relevant information, thoughts or actions while ignoring irrelevant or scattered stimuli. Thus, attention allows the organism to interact in a proper way with the environment. Among the brain structures associated with the control of attention, the Dorsolateral Prefrontal Cortex (DLPFC) has a remarkable role in current literature as a region associated with behavioral control. Transcranial Direct Current Stimulation (TDCS) is based on the application of a low intensity electric current through electrodes placed in the scalp, aimed at modulating the activity of different brain areas. This technique has been used to study brain functions. This study has the objective of verifying how attention can be modulated through the application of bilateral tDCS on DLPFC using measures of reaction time (RT) in tasks of temporal and spatial orientation. To accomplish that, two experiments were planned and executed. In the first one, which focused on the voluntary orienting of spatial attention, each participant had to orient attention to the position indicated by an arrow; in the second, on voluntary orienting of temporal attention, each participant had to orient attention to the most frequent time interval of visual targets. In both cases, participants had to respond as fast as possible when the target was displayed by pressing a joystick key. RTs were registered. The sample was composed of 18 undergraduate students, age range 19-25 years old (12 for the first experiment and 6 more for the second). In each experiment, subjects were submitted to three tDCS conditions (anodal, cathodal and sham) on the DLPFC during the undertaking of tests. Analyses of variance were made, in order to compare the involved factors. For the experiment of spatial orientation, the anodal condition produced lower RTs, when compared to sham. For the temporal orienting experiment it was observed that, in the anodal modulation, RTs were increased for the less frequent interval (500 ms), indicating that the anodal tDCS can have influenced in a more effective way attentional orienting to the most frequent intervals. Therefore it is possible to postulate the existence of a facilitating effect of anodal tDCS in the modulation of DLPFC, which generated an impact in attentional orienting, lowering RTs to the valid condition (spatial) when compared to sham tDCS.